Contemporary Action Theory Volume 1: Individual Action
XVII, 317 p. 2 illus.
Keywords: Contemporary Action Theory, Volume I (Individual Action) is concerned with topics in philosophical action theory such as reasons and causes of action, intentions, freedom of will and of action, omissions and norms in legal and ethical contexts, as well as activity, passivity and competence from medical points of view. Cognitive trying, freedom of the will and agent causation are challenges in the discussion on computers in action. The Volume consists of contributions by leading experts in the field written specifically for this volume. No comparable volume currently exists.